2022
DOI: 10.37506/ijfmt.v16i3.18257
|View full text |Cite
|
Sign up to set email alerts
|

Does the Proximity of the Area Affect in Incidence of Stunting? : Study on Densely Populated Provinces in Indonesia

Astridya Paramita,
Nailul Izza,
DwiHapsari Tjandrarini
et al.

Abstract: The prevalence of stunting in Indonesia is still above WHO standards, so it needs to be addressed immediately, given the adverse effects on individuals and countries. This study aims to analyze the incidence of stunting in East Java by paying attention to the proximity of the area as an effort to solved stunting problems. The study was conducted using secondary data from 2017 from official government agency reports. Administrative area (regency/city) analysis unit. Analysis using spatial regression test. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Based on the type of residence, the study found children in rural areas were more likely to be stunted than those in urban areas. It was in line with the previous research that stunting probably suffered more by countryside children than by cities in Indonesia (Laksono, Sukoco, et al, 2022;Paramita et al, 2022). Other studies in Indonesia also discovered a higher stunting proportion of children under two years old in the countryside than in the city Laksono et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Based on the type of residence, the study found children in rural areas were more likely to be stunted than those in urban areas. It was in line with the previous research that stunting probably suffered more by countryside children than by cities in Indonesia (Laksono, Sukoco, et al, 2022;Paramita et al, 2022). Other studies in Indonesia also discovered a higher stunting proportion of children under two years old in the countryside than in the city Laksono et al, 2020).…”
Section: Discussionsupporting
confidence: 91%